Primary and aggregate color centers in proton irradiated LiF crystals and thin films for luminescent solid state detectors. Issue 1 (March 2015) - Piccinini, M; Ambrosini, F; Ampollini, A; Bonfigli, F; Libera, S; Picardi, L; Ronsivalle, C; Vincenti, M A; Montereali, R M
Abstract: Proton beams of 3 MeV energy, produced by the injector of a linear accelerator for proton therapy, were used to irradiate at room temperature lithium fluoride crystals and polycrystalline thin films grown by thermal evaporation. The irradiation fluence range was 10 11 -10 15 protons/cm 2 . The proton irradiation induced the stable formation of primary and aggregate color centers. Their formation was investigated by optical absorption and photoluminescence spectroscopy. The F2 and F3 + photoluminescence intensities, carefully measured in LiF crystals and thin films, show linear behaviours up to different maximum values of the irradiation fluence, after which a quenching is observed, depending on the nature of the samples (crystals and films). The Principal Component Analysis, applied to the absorption spectra of colored crystals, allowed to clearly identify the formation of more complex aggregate defects in samples irradiated at highest fluences.